PERBAIKAN LAYANAN PERPUSTAKAAN TERHADAP PENINGKATAN MINAT BACA SISWA DI UPTD SMP NEGERI 3 BIREUEN - Jufni; Cahya Anjani (Fakultas Tarbiyah IAI Almuslim Aceh, 2023)
The formulation of the problem in the discussion of this journal is what is the general description of UPTD SMP Negeri 3 Bireuen, what is the theoretical study of improving library services on increasing students' interest in reading, how does improving library services increase students' interest in reading at UPTD SMP Negeri 3 Bireuen. This research uses qualitative research with the type of field research. Data collection was carried out by means of observation, interviews and documentation. The research findings inform: First, regarding the general description of the UPTD of SMP Negeri 3 Bireuen which is one of the educational units at the junior high school level which is located at Bireuen Meunasah Reulet, Kota Juang District, Bireuen Regency. then includes the school background, vision, mission and goals, organizational structure, condition of teachers and students, as well as adequate facilities and infrastructure to support an orderly and sustainable learning process. Second, a theoretical study of improving library services to increase reading interest. Third, improving library services to increase students' interest in reading at UPTD SMP Negeri 3 Bireuen includes improving library services, namely forming a reading club, forming a writer's club, opening an arts and culture gallery service, and opening a life skills service. The obstacles faced in increasing students' interest in reading are the learning system, lots of more interesting entertainment and games, lots of entertainment venues, limited library space. Efforts to increase interest in reading include creating a reading corner in class, inviting people to visit the library, reading before starting learning, giving books as rewards to students and creating a digital library.